Child abuse: Cross-sectional survey of general dentists - Harsimran Kaur; Seema Chaudhary; Nidhi Choudhary; Naveen Manuja; T.R. Chaitra; Sinha Ashish Amit (Elsevier, 2016)
Background: Child abuse continues to be a social menace causing both physical and emotional trauma to benevolent children. Census has shown that nearly 50-75% of child abuse include trauma to mouth, face, and head. Thus, dental professionals are in strategic position to identify physical and emotional manifestations of abuse. Aim: A cross-sectional survey was undertaken to assess knowledge and attitude of dental practitioners regarding child abuse and to identify the barriers in reporting the same. Methods: With prior consent, a 20-question survey including both multiple choice and dichotomous (Yes/No) questions was mailed to 120 state-registered general dentists, and the data collected were subjected to statistical analysis. Results: Overall response rate to the questionnaires was 97%. Lack of knowledge about dentist's role in reporting child abuse accounted to 55% in the reasons for hesitancy to report. Pearson chi-square test did not show any significant difference between male and female regarding reason for hesitancy to report and legal obligation of dentists. Conclusion: Although respondent dentists were aware of the diagnosis of child abuse, they were hesitant and unaware of the appropriate authority to report. Increased instruction in the areas of recognition and reporting of child abuse and neglect should be emphasized.